Part-time and temporary employment in modern conditions: Scope and priorities of social protection - Orynbassarova, Y.; Serikova, G.; Pritvorova, T.; Legostayeva, A.; Kuttybaeva, N.; Komekbayeva, L. (Entrepreneurship and Sustainability Issues, 2019)
The article considers the factors acting in the post-industrial economy both on the demand side for labor and on the supply side, which determined a sufficient number of options for deviation from the standard schedule, the most widespread of which include temporary employment, part-time employment and self-employment. If the first two types are options for non-standard employment for employees, the latter is allocated to a special employment status, which differs from the status of "employee" on a number of clear criteria. It is concluded that the burden on part-time workers has decreased, which is one of the signs of an impending crisis, when they reduce the number and length of working time for part-time workers, refusing their services in the first place. At the same time, the growth of over-employment again speaks of the desire of people to save their jobs through overtime work. According to the results of our study, we have developed proposals for enhancing the social protection of temporary and part-time workers.
Keywords: social protection; employment; non-standard employment; economy